The Role of the Nurul Hayat Gresik Amil Zakat Institute (Laz) in Empowering Rural Communities During the Covid-19 Pandemic - Muhammad Hamzah Rabani; Ach. Yasin (Universitas Muhammadiyah Enrekang, 2023)
The spread of the pandemic-19 has resulted in the increasing of poor residents in Gresik Regency and East Java Province, up to 2021 (gresikkab.bps.go.id and jatim.bps.go.id). seeing the magnitude impact of the Covid-19 in all aspect, efforts are needed concrete solutions that can solve these problems in the form of empowerment village community (Aprilianto, et al, 2021). This problem requires support from institutions referred to Lembaga Amil Zakat (LAZ) Nurul Hayat (Rohmah, 2021). This institution is an that collect Zakat, Infaq, and Shadaqah (SIZ) funds f rom the community (muzakki) and redistributed to the community (mustahiq) according to islamic law. The purpose of this research is to find out of the role of Lembaga Amil Zakat Nurul Hayat Gresik institution in empowering village communities during the pandemic covid-19. This research is a descriptive qualitative techniques of taking the subject using purposive sampling. Data collection techniques from interviews, observations, and documentations. The results of this study indicate that the existance of LAZ Nurul Hayat Gresik empowerment program has made the community more advanced and developed in their socio-economic field, the village community feels that they have gained more scientific insight related to entrepreneurship practices. The empowerment program from LAZ Nurul Hayat: namely Ternak Desa Sejahtera (TDS) program, and Micro, Small, Medium Enterprises (MSMEs) program.